2021
DOI: 10.3390/ph14030220
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol (CBD) Alters the Functionality of Neutrophils (PMN). Implications in the Refractory Epilepsy Treatment

Abstract: Cannabidiol (CBD), a lipophilic cannabinoid compound without psychoactive effects, has emerged as adjuvant of anti-epileptic drugs (AEDs) in the treatment of refractory epilepsy (RE), decreasing the severity and/or frequency of seizures. CBD is considered a multitarget drug that could act throughout the canonical endocannabinoid receptors (CB1-CB2) or multiple non-canonical pathways. Despite the fact that the CBD mechanism in RE is still unknown, experiments carried out in our laboratory showed that CBD has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…CBD’s ability to modulate PMN extravasation has been examined in several in vitro models of migration. For example, McHugh and colleagues found that CBD inhibited fMLP-induced migration of human PMNs in a concentration-dependent manner [ 153 ], and the results of this study were also confirmed in a similar model by Gómez and colleagues [ 154 ], Mukhopadhyay et al [ 155 ], and Mabou Tagne et al, who showed that CBD inhibits PMN migration after activation with IL-8, but not in resting cells, in a concentration-dependent manner [ 156 ]. This finding is, in our opinion, of extreme interest, because it seems to suggest that CBD’s anti-inflammatory effects are greater in pathological conditions, whereas this compound does not seem to exert an inhibitory effect on the immune system in physiological conditions, thus once again highlighting the safety and manageability of CBD.…”
Section: Effects Of Cbd On Immune Systemssupporting
confidence: 77%
See 1 more Smart Citation
“…CBD’s ability to modulate PMN extravasation has been examined in several in vitro models of migration. For example, McHugh and colleagues found that CBD inhibited fMLP-induced migration of human PMNs in a concentration-dependent manner [ 153 ], and the results of this study were also confirmed in a similar model by Gómez and colleagues [ 154 ], Mukhopadhyay et al [ 155 ], and Mabou Tagne et al, who showed that CBD inhibits PMN migration after activation with IL-8, but not in resting cells, in a concentration-dependent manner [ 156 ]. This finding is, in our opinion, of extreme interest, because it seems to suggest that CBD’s anti-inflammatory effects are greater in pathological conditions, whereas this compound does not seem to exert an inhibitory effect on the immune system in physiological conditions, thus once again highlighting the safety and manageability of CBD.…”
Section: Effects Of Cbd On Immune Systemssupporting
confidence: 77%
“…Lastly, Gómez found that CBD triggered a significant decrease in oxygen uptake and H 2 O 2 generation but also increased ROS production. In order to explain this discrepancy, the authors postulated that CBD might activate different receptors present on PMNs, which in turn modulate different intracellular pathways, causing these apparently contradictory effects [ 154 ].…”
Section: Effects Of Cbd On Immune Systemsmentioning
confidence: 99%
“…Previous literature shows that CBD inhibits neutrophil migration and infiltration in vivo and vitro ( Mabou Tagne et al, 2019 ; Gómez et al, 2021 ; Robaina Cabrera et al, 2021 ). Thus, treatment with CBD may ameliorate excessive inflammatory responses involving neutrophils.…”
Section: Inhibition Of Ros/rns Generation By Cbd: Relevance For Ichmentioning
confidence: 94%
“…CBD interferes with the translocation of the NOX2 subunits to the membrane, preventing the oxidative burst and, consequently, the generation of O2− and H2O2 [ 104 ]. Additionally, CBD reduces neutrophil activation and degranulation [ 128 ].…”
Section: Cbd Modulates Inflammatory Cell Functionsmentioning
confidence: 99%